FINITE STRAIN ANALYSIS OF LIMESTONE/BASALTIC MAGMA INTERACTION AND FRACTURE: LOW ORDER MIXED TETRAHEDRON AND REMESHING - AREIAS, P. (2019)
In this investigation, we use a recent constitutive framework and remising technique for tetrahedra to analyse the pressure-driven crack propagation of limestone intruded by basaltic magma. Limestone is represented by an least-plastic capped Drucker-Prager model with an hypo elastic term in order to account for inelastic effects from plastic signature. Kinematic hardening is considered for limestone, whereas magma is modelled by means of a compressible Bingham fluid. Classical limit surfaces of the capped model are used to initiate the crack events in the limestone. Propagation is performed by a local remising technique with mesh smoothing for untracked elements. Arnold's MINI element is used to avoid locking in the quasi-incompressible case. Verification (for limestone) examples and a crack propagation example in 3D are performed. A mesh convergence study is performed, exhibiting very promising results.